Metabolic incorporation of H218O into specific glucose‐6‐phosphate oxygens by red‐blood‐cell lysates as observed by 13C isotope‐shifted NMR signals. (12th August 2020) - Coelho, Margarida; Barosa, Cristina; Tavares, Ludgero; Jones, John G.
Abstract : Water enriched with oxygen‐18 (H2 18 O) is a potential tracer for evaluating the sources of glucose and glycogen synthesis since it is incorporated into specific sites of glucose‐6‐phosphate via specific enzyme‐mediated exchange/addition mechanisms. Unlike 2 H, 18 O does not experience significant isotope effects for any of these processes. Therefore, H2 18 O might provide more precise estimates of endogenous carbohydrate synthesis compared with deuterated water provided that positional 18 O enrichments of glucose can be measured. As a proof of concept, H2 18 O was incorporated into a well characterized hemolysate model of sugar phosphate metabolism and 13 C NMR was applied to quantify positional 18 O enrichment of glucose‐6‐phosphate oxygens. Human erythrocyte hemolysate preparations were incubated overnight at 37 °C with a buffer containing sugar phosphate precursors and 20% ( n = 5) and 80% ( n = 1) H2 18 O. Enrichment of glucose‐6‐phosphate was analyzed by 13 C NMR analysis of 18 O‐shifted versus unshifted signals following derivatization to monoacetone glucose (MAG). 13 C NMR MAG spectra from hemolysate revealed resolved 18 O‐shifted signals in Positions 1‐5. Mean 18 O enrichments were 16.4 ± 1.6% (Position 1), 13.3 ± 1.3% (Position 2), 4.1 ± 1.1% (Position 3), 12.6 ± 0.8% (Position 4), 10.7 ± 1.4% (Position 5), and no detectable enrichment of Position 6. No 18 O‐shifted glucose‐6‐phosphate signals were detected in preparations containing sugar phosphate precursors only. H2 18 O is incorporated into Positions 1‐5 of glucose‐6‐phosphate in accordance with spontaneous aldose hydration and specific enzymatic reaction mechanisms. This provides a basis for its deployment as a tracer for glucose and glycogen biosynthesis. Abstract : Water enriched with 18 O is a potential tracer for evaluating endogenous glucose and glycogen synthesis. We demonstrate that 18 O labelling of glucose can be observed by 13 C NMR analysis, where carbons bound to 18 O are shifted upfield from those bound to 16 O. This analysis was applied to erythrocyte hemolysates that were provided with H2 18 O and sugar phosphate intermediates to initiate 18 O‐exchange reactions. By derivatizing glucose, we could quantify the incorporation of this tracer into the various positions of glucose‐6‐phosphate.